Odpowiedzi

2009-09-05T13:46:18+02:00
(x³+9x²+36x+108)(x-3)=0
x²(x+9)+18(2x+6)(x-3)=0
(x²+18)(x+9)(2x+6)(x-3)=0
(x²+18)=0 ∨(x+9)=0 ∨(2x+6)=0 ∨ (x-3)=0
x₁∈{należy} do zbioru pustego (nie ma takiego rozwiązania)
∨ x₂=-9 ∨ x₃=-3 ∨ x₄=3
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-05T14:13:17+02:00
(x³+9x²+36x+108)(x-3)=0
rozdzielam pierwszy nawias
x²(x+9)+18(2x+6)(x-3)=0
teraz grupuje co za nawiasem
(x²+18)(x+9)(2x+6)(x-3)=0
x²+18=0
1)x²=-18
brak rozwiązania
2)x+9=0
x=-9
3)2x+6=0
2x=-6
x=-3
4)x-3=0
x=3
x₁ ∈do zbioru pustego ∨ x₂=-9 ∨ x₃=-3 ∨ x₄=3
pozdrawiam dagmara